Design of a fully integrated receiver analog baseband chain for 2.4-GHz ZigBee applications. (June 2016) - Yang, Yin-Tang; Shi, Zuo-Chen; Li, Di; Wang, Yu
Abstract: A receiver analog baseband (ABB) chain for an integrated ZigBee (IEEE 802.15.4) transceiver is presented in this paper. The ABB is composed by a 3rd-order complex band-pass filter (BPF), a variable gain amplifier (VGA) and an analog-to-digital converter (ADC). The circuit topology of each building block has been designed complying with the IEEE 802.15.4 standard as well as featuring low power consumption and small chip size. In this work, a mixed-signal frequency auto-tuning scheme is proposed for complex BPF to accommodate the performance deterioration due to the process, voltage and temperature (PVT) variations. A novel method combined opamp- and capacitor-sharing is presented for ADC to obtain low power consumption and elimination of memory effect. The proposed ABB demonstrates 70 dB dynamic range by 2 dB/step, 12 dBm IIP3 and 35.2 nV/√Hz input referred noise. The measured SNDR and SFDR are 41.9 dB and 58.7 dB, respectively. Implemented in a standard 0.18-μm CMOS technology, the entire receiver ABB chain occupies an area as small as 1.5 mm 2 and the total power consumption is only 16 mW at max gain setting from a 1.8 V supply.